HUBUNGAN PAPARAN MEDIA PORNOGRAFI DENGAN PERILAKU SEKSUAL PRANIKAH PADA REMAJA - Tripayana, I Nyoman Dyana; Sanjiwani, Ida Arimurti; Nurhesti, Putu Oka Yuli (Coping: Community of Publishing in Nursing; Vol 9 No 2 (2021): April 2021, 2021)
Adolescence is a period that is passed by every individual, this phase occur from children to adults. This condition causes a variety of problems prone. Adolescents may perceive problems namely sexual act. The high incidence of sexual act on adolescents is still a serious concern. It can be influenced by the telecommunication media and sexual desires thus adolescents are increasingly vulnerable to exposure to the negative things, such as pornography media exposure. The high intensity of pornography media utilization consequently induces adolescent to practice the act that have been seen or watched. The purpose of this study was to determine the relationship of pornography media exposure to pre-marital sexual behavior in adolescents at the Dalung Tourism Vocational School. This research conducted during March-June 2020. This research was a correlative descriptive study. This study employed 157 students that obtained through probability sampling techniques. Pornographic media exposure and pre-marital sexual behavior measured by using a questionnaire. The Spearman correlation test was used in this study for data analysis. Based on the results of the study, it was found that a significant and positive relationship between pornography media exposure with adolescent pre-marital sexual behavior (p <0.05). Pornography media has a crucial role to trigger pre-marital sexual behavior of the adolescent however it causes adolescents to confront with other problems that can affect adolescents’ growth and development thus to address this issue, teenagers need positive information to anticipate pre-marital sexual behavior problems.